Synthesis of ZnO/Bi-doped porous LaFeO3 nanocomposites as highly efficient nano-photocatalysts dependent on the enhanced utilization of visible-light-excited electrons - Humayun, Muhammad; Sun, Ning; Raziq, Fazal; Zhang, Xuliang; Yan, Rui; Li, Zhijun; Qu, Yang; Jing, Liqiang (Applied catalysis. B, Environmental, 2018)
Improved visible-light activities of porous LaFeO3 are attributed to coupled ZnO for accepting electrons and to doped Bi3+ to extend visible-light absorption. [Display omitted] •ZnO/Bi-doped porous LaFeO3 nanocomposite has been successfully synthesized.•It exhibits high visible-light photoactivities for 2,4-DCP degradation and CO2 conversion.•Its high photoactivity is attributed to enhanced utilization of visible-light-excited electrons.•Electron utilization enhancement results from optical extension by Bi3+ doping and electron transfer to ZnO.•Possible decomposition pathways of 2,4-DCP over different photocatalysts are proposed. ZnO coupled Bi-doped porous LaFeO3 nanocomposites have successfully been fabricated via a wet-chemical method. It is confirmed that Bi3+ enters into the crystal lattice of PLFO and substitute La3+, while the ZnO with diameter of ∼15 nm is coupled to the Bi-doped PLFO. It is shown that the amount-optimized 5Zn/7Bi-PLFO nanocomposite exhibits greatly improved visible-light activities for 2,4-dichlorophenol (2,4-DCP) degradation and CO2 conversion, compared to the unmodified PLFO with rather high photoactivity due to its large specific surface area. Based on the measurements of valence band XPS spectra, steady-state surface photovoltage spectra, transient-state surface photovoltage responses, photoelectrochemical I–V curves, fluorescence spectra related to produced OH amount and photocurrent action spectra, it is clearly demonstrated that the significantly improved visible-light activities are attributed to the enhanced utilization of visible-light-excited high-level-energy electrons (HLEEs) by coupling with nanocrystalline ZnO to introduce a new energy platform for accepting electrons and to the extended visible-light absorption by doping Bi3+ to create surface states. Interestingly, it is proved that under UV–vis irradiation, the amount-optimized nanocomposite exhibit much higher photoactivity for 2,4-DCP degradation compared to the commercially available P25 TiO2. Moreover, it is confirmed by means of radical trapping experiments that the dominant radicals to decompose 2,4-DCP on PLFO could be modulated by doping Bi3+ and coupling ZnO. Furthermore, the possible decomposition pathways, respectively related to the OH and O2−, of 2,4-DCP over the amount-optimized Bi-doped PLFO and ZnO coupled Bi-doped PLFO samples are proposed by means of the liquid chromatography tandem mass spectrometry analysis of the intermediates, especially with the used isotopic D2O.